Differentiated Instruction in Islamic Senior High School: Aspects, Strategies and Problems - Wanda Hijriani Herwanto; Hamdatul Musyarrofah (Universitas Muhammadiyah Mataram, 2024)
Understanding the implementation of Differentiated Instruction is crucial, especially where Islamic high schools adopt a distinct educational approach in implementing the Emancipated Curriculum, making it essential to understand the nuances of this approach to enhance student learning outcomes effectively. This study investigates the aspects and strategies applied as well as the problems faced by English Teachers of Islamic Senior High Schools in implementing differentiated instruction. A descriptive qualitative study was utilized through semi-structured interviews with five English teachers from different schools and document analysis of the teachers’ lesson plans. The process of thematic analysis involved coding and categorizing the answers from the participants into themes, which were then compared with the document analysis and interpreted. The findings indicated that all aspects have been applied in the implementation of differentiated instruction including content, process, product, and learning environment. Diverse strategies were applied, such as presenting materials in different forms, implementing collaborative projects, peer tutoring, adapting Islamic stories and histories, etc. However, the teachers faced problems in managing time, selecting relevant materials, developing distinct assessment rubrics, etc. This study contributes to the understanding of the implementation of differentiated instruction in English language learning, in the context of Islamic secondary schools by providing practical strategies and adding insight into existing literature. The study suggests that implementing differentiated instruction with all its aspects and teachers can adapt various strategies to cater to diverse student needs.